Approaching the bishop: pastors and cultural brokers - Wassenaar, Jelle (2017)

Beyond nation-building: “patria” and belonging in the tenth century - Wassenaar, Jelle (2017)

Bishops, Canon Law, and the Politics of Belonging in Post-Carolingian Italy, c. 930-c. 960 - Wassenaar, Jelle (Using and Not Using the Past after the Carolingian Empire c. 900–c.1050, 2019)
Both modern scholarship and contemporary accounts have portrayed the tenth-century Italian episcopacy as more divided than its counterparts in West and East Francia. This chapter will argue that ideals of episcopal unity and solidarity were more prevalent among northern Italian prelates than implied by these accounts. While church councils and other more overt displays of episcopal solidarity were largely absent, an ideology of episcopal collegiality was kept alive through the production and transmission of canon law collections. Moreover, appealing to the episcopacy as an ordo was still endowed with a great deal of political power<br

Clerical solidarity and King Hugh’s hirelings in Rather of Verona’s Praeloquia - Wassenaar, Jelle (2018)

Making Ends Meet. Cross-Cultural Perspectives on the End of Times in Medieval Christianity, Islam, and Buddhism - Frauschner, Anna; Wassenaar, Jelle; Wieser, Veronika (Medieval Worlds, 2016)

Middeleeuws computeren - Wassenaar, Jelle; Waagmeester, Bastiaan (Perkament in stukken. Teruggevonden middeleeuwse handschriftfragmenten, 2018)

The Christmas messages of tenth-century bishops - Wassenaar, Jelle (2018)

The tenth-century episcopacy as a commonwealth of learning - Wassenaar, Jelle (2018)

Townspeople, Group Belonging, and Collective Agency in Post-Carolingian Historiography - Wassenaar, Jelle (The Past Through Narratology: New Approaches to Late Antiquity and the Early Middle Ages, 2022)
This article deals with depictions of townspeople in tenth- and early eleventh-century narratives. It argues that during the tenth century the narrative function of these groups in historiography changed fundamentally. In Carolingian and earlier tenth-century narratives, townspeople tend to play largely tangential and passive roles; from around the middle of the tenth century, authors began to increasingly accord agency and a more central role to townspeople. Although these mentions of townspeople in post-Carolingian histories have traditionally been approached as providing a window into processes of ‘embryonic’ urbanisation, this paper suggests that the shift in their narrative function must also be understood in the context of the changing nature of diocesan identity politics created through the dissolution of the Carolingian Empire.<br

Transforming Irish Traditions: De XII abusiuis saeculi and Justice in the Frankish World, c. 750-1050 - Wassenaar, Jelle (Addressing Injustice in the Medieval Body Politic, 2023)

Uses of the Past in Times of Transition. Forgetting, Using, and Discrediting the Past - Wassenaar, Jelle (2019)